(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the results of posterior vocal cord resection surgery using a suction cutter in the treatment of bilateral vocal cord paralysis in the closed position. Subjects: 21 patients diagnosed with bilateral vocal cord paralysis in the closed position were treated with posterior vocal cord resection using a suction cutter at the Emergency Department, National Otorhinorarynology Hospital of Vietnam from September 2023 to August 2024. Research method: Prospective. Results: Patients with previous tracheostomy were able to remove the cannula a few days after surgery. After surgery, 85.72% of patients, 90.48% of patients no longer had difficulty breathing and had a glottis width > 5 mm; 66.67% of patients had mild or moderate voice disorders. Conclusions: Surgery to resect the posterior part of the vocal cords with a suction cutter gives good results, both resolving dyspnea and preserving speech function, improving the patient’s quality of life, short surgery time, and causing few complications.